2016
DOI: 10.1186/s13567-016-0374-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of epitopes recognised by mucosal CD4+ T-cell populations from cattle experimentally colonised with Escherichia coli O157:H7

Abstract: Vaccines targeting enterohaemorrhagic Escherichia coli (EHEC) O157:H7 shedding in cattle are only partially protective. The correlates of protection of these vaccines are unknown, but it is probable that they reduce bacterial adherence at the mucosal surface via the induction of blocking antibodies. Recent studies have indicated a role for cellular immunity in cattle during colonisation, providing an impetus to understand the bacterial epitopes recognised during this response. This study mapped the epitopes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Nevertheless, T-cells from VAC+ animals, which we consider to have been less exposed to Stx, tended to respond more vigorously to ConA in week 16. Stx inhibits the immunogenic effect of systemically administered antigen [ 49 ] and Kieckens et al as well as Corbishley et al showed that STEC colonization affect cattle’s general immune response [ 50 , 51 ] suggesting that Stx impairs immune responses in cattle in a more general manner than currently recognized.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, T-cells from VAC+ animals, which we consider to have been less exposed to Stx, tended to respond more vigorously to ConA in week 16. Stx inhibits the immunogenic effect of systemically administered antigen [ 49 ] and Kieckens et al as well as Corbishley et al showed that STEC colonization affect cattle’s general immune response [ 50 , 51 ] suggesting that Stx impairs immune responses in cattle in a more general manner than currently recognized.…”
Section: Discussionmentioning
confidence: 99%
“…However, a 1-bp deletion in the DRB1*13:01 allele generated a mixed sequence from which the alleles could not be unambiguously identified. Therefore, the forward primer 455_F, a modification described in Corbishley et al ( 2016 ) which sits downstream of the deletion, was used in preference (Table 1 ). Between 27 and 31 sheep were randomly selected from each of four cohorts (1993, 1998, 2003, 2008) and genotyped to identify DRB1 homozygous individuals for subsequent analysis of DQ diversity, with the expectation that DRB1 homozygotes were more likely to be homozygous at DQ loci due to linkage disequilibrium.…”
Section: Methodsmentioning
confidence: 99%
“…A number of STEC O157 antigens have been identified as potential vaccine candidates and subunit vaccines. To date, two vaccines have been developed and licensed; Econiche (Econiche Corp, Belleville, Canada) is based on type III secreted proteins (T3SPs) and Epitopix (Willmar, USA) comprises cell membrane extracts prepared from iron restricted cultures (Corbishley et al., ). Although both vaccines induce antibody responses effective in significantly reducing colonization, they are only partially protective (Snedeker, Campbell, & Sargeant, ).…”
Section: Prevention and Controlmentioning
confidence: 99%
“…Considerable research effort is going into the development of new vaccines by identifying alternative vaccine candidates, such as flagella, the EhaB autotransporter protein and proteins associated with T3SS‐mediated adherence (Mahajan et al., ; McNeilly et al., ; Wells et al., ). In addition, efforts have been undertaken to improve vaccine efficiency, such as by including vaccine candidates that induce a cellular response (Corbishley et al., ). The ongoing mining of WGS data (Lupolova et al., ) may allow vaccine development to focus on vaccine candidates expressed only by virulent STEC.…”
Section: Prevention and Controlmentioning
confidence: 99%